Pengembangan Model Kolaborasi Ekonomi Berbasis Sekolah Kejuruan - Sulaeman Deni Ramdani; Agung Hanfi Astana; Moh Fawaid (Jurnal Taman Vokasi, 2019)
Abstracts. The ASEAN Economic Community (AEC) encourages competition in the fields of human, economic, technological and industrial resources. MEA has the potential to open up opportunities and more challenging expectations and force to work hard to be able to take roles and opportunities in the competition. The purpose of this study are 1) developing a vocational school-based economic collaboration model, 2) knowing the feasibility of a vocational school-based economic collaboration model. This research is a research and development study using the 4D model, namely define, design, develop, and disseminate. Data comes from literature and questionnaire studies. Research data analysis techniques using descriptive statistical analysis. The results of the study show that the model of economic collaboration based on vocational schools requires collaboration and collaboration between institutions and the community to create sustainable and mutually beneficial synergy. Vocational school-based economic collaboration models produce collaborative models that involve industry, retail, MSMEs, farmer groups, and start-ups. Expert assessment of the collaboration model falls into the "very appropriate" category. The implementation of collaboration needs to consider several aspects, namely regional characteristics, local government regulations, school readiness, community readiness, and local industry characteristics.